FOURTH SPACE: Sonic & /aural dimensions of Cape Town's historic urban landscape - Lehloenya, Mahoati Arthur (School of Architecture, Planning and Geomatics, 2023)
Focusing on the urban enclave of Cape Town, informally known as the City Bowl, this thesis examines the significance of historic city soundscapes that give shape to its urban heritage. At the levels of international, national, and local governance and in policy documentation, little attention is given to the ‘immaterial', with sound especially not seen as inherently significant to cultural heritage. The study draws on Sabine Marshall's concept of ‘Official' and ‘Vernacular' forms of heritage as its conceptual framework of ‘Sound' and ‘Noise' as a way of gauging public perception of sound that matters versus sound as noise. Further, it evaluates the relationships people have with Eurocentric forms of sonic representations that are imbued with monumentality alongside those of African traditions and practices. The two divergent frameworks in sound studies, that of sound versus that of noise, illuminate the tensions of colonialism and coloniality, and the reinforcement of systems of inequality and imbalances of legislation in heritage preservation. In this thesis, I use ethnography in combination with qualitative research methods such as interviews and survey data as my research methods. Two urban heritage sounds are studied comparatively: the Noon Gun, located on Signal Hill (Lion's Rump), and the Adhan call-to-prayer that sounds from the mosques of Cape Town. The significance of the case studies are assessed using a physical, historical and social (PHS) model of the cultural value of soundscapes for cultural heritage. The interdisciplinary approach of sound theory and heritage studies is used to probe the production of sound and its consumption by its listeners. This thesis therefore offers insight into how the city and its residents mediate heritage claims and how the city residents interpret and understand them. This dissertation is an invitation for an alternative mode of perception, that of hearing, as a methodological response to the heritage canon. More specifically, I analyse the meaning of sound and its physical, historical, social and political facets in production, consumption, politicisation and contestation in the city of Cape Town. A study of sound I argue is therefore crucial to the body of knowledge on heritage significance in Cape Town and beyond.